(untitled) (Research, Society and Development, 2021)
Aim. To evaluate the quality of Primary Health Care (PHC) models for Brazilian children. Methods. A cross-sectional study was performed with 516 parents or guardian of children in the public preschools from a city in São Paulo State, Brazil. The participants completed the questionnaires on the perception of the quality of the PHC (Primary Care Assessment Tool-PCATool), and the socioeconomic conditions in their families. The data were analyzed by statistical tests (95% confidence level). Results. Private services, Family Health Strategies (FHS), and Conventional Health Care (CHC) were the modalities of PHC used by children. Among the three modalities, in all groups were observed statistically significant differences (p<0.001), the best quality of care was provided by FHS (8.22±1.69). The CHC (5.69±1.34) and the private service (6.65±0.99) need improvement in accessibility, continuity of care, integrality, family, and community orientation. The socioeconomic class of the families was associated with modalities of PHC (p<0.001). Conclusions. The quality of primary care for children in the public health system still requires much improvement, primarily in conventional model. However, the Family Health Strategies was the model that presented the best quality of primary health care for children.